Pengaruh Keamanan dan Kualitas Pelayanan Terhadap Reputasi Dalam Belanja Online Pada Millennials di Shopee - Arfandi Viko Widana; Widarto Rachbini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The security aspect is an important element in online transactions, covering personal data protection, secure payment systems, and user protection policies designed to provide comfort and a sense of security when transacting. In addition, service quality, which includes quick response, ease of access, service friendliness, and delivery accuracy, plays a significant role in building Shopee's reputation as the millennial generation's favorite e-commerce platform. The results of quantitative analysis with a multiple linear regression approach show that service quality has a greater influence than security in shaping the platform's reputation. These findings highlight the importance for Shopee to continue to innovate in improving service quality and strengthening the security system in order to maintain customer trust, increase loyalty, and strengthen its position amid the increasingly dynamic e-commerce market competition.